Graphene Oxide Nanosheets Interact and Interfere with SARS‐CoV‐2 Surface Proteins and Cell Receptors to Inhibit Infectivity. Issue 25 (14th May 2021) - Unal, Mehmet Altay; Bayrakdar, Fatma; Nazir, Hasan; Besbinar, Omur; Gurcan, Cansu; Lozano, Neus; Arellano, Luis M.; Yalcin, Süleyman; Panatli, Oguzhan; Celik, Dogantan; Alkaya, Damla; Agan, Aydan; et al.
Abstract: Nanotechnology can offer a number of options against coronavirus disease 2019 (COVID‐19) acting both extracellularly and intracellularly to the host cells. Here, the aim is to explore graphene oxide (GO), the most studied 2D nanomaterial in biomedical applications, as a nanoscale platform for interaction with SARS‐CoV‐2. Molecular docking analyses of GO sheets on interaction with three different structures: SARS‐CoV‐2 viral spike (open state – 6VYB or closed state – 6VXX), ACE2 (1R42), and the ACE2‐bound spike complex (6M0J) are performed. GO shows high affinity for the surface of all three structures (6M0J, 6VYB and 6VXX). When binding affinities and involved bonding types are compared, GO interacts more strongly with the spike or ACE2, compared to 6M0J. Infection experiments using infectious viral particles from four different clades as classified by Global Initiative on Sharing all Influenza Data (GISAID), are performed for validation purposes. Thin, biological‐grade GO nanoscale (few hundred nanometers in lateral dimension) sheets are able to significantly reduce copies for three different viral clades. This data has demonstrated that GO sheets have the capacity to interact with SARS‐CoV‐2 surface components and disrupt infectivity even in the presence of any mutations on the viral spike. GO nanosheets are proposed to be further explored as a nanoscale platform for development of antiviral strategies against COVID‐19. Abstract : Detailed in silico and in vitro tools are applied to show that graphene oxide is able to interact effectively with the SARS‐CoV‐2 surface proteins and receptors leading to an infection inhibitory action. Four viral clades are used to determine inhibition of viral infection following mutations in the viral proteins.